A cross-sectional survey on ZIKV in Honduras: Implications for governance and risk communication approaches. Issue 2 (5th June 2017) - Rosales, Alfonso; Yepes-Mayorga, Adriana; Arias, Alejandro; Franz, Fabiano; Thomas, Joanne; Huddle, Jamo; Soto, Ramón Jeremías; Haynes, Maya; Prado, Monica; Cherian, Dennis
Abstract : Purpose: Zika virus (ZIKV) statistics in Honduras are the highest among countries in Central America. National risk communication strategies have primarily focused on vector control and are integrated into existing approaches for Dengue and Chikungunya. Given the new evidence on ZIKV, there is a need to revamp risk communication strategies so that they are informed by dynamic listening methods such as knowledge, attitudes, and practices. The paper aims to discuss this issue. Design/methodology/approach: A cross-sectional survey was administered to 604 respondents in 21 designated Honduran communities using a two-stage, 30-cluster sampling method. Findings: Almost eight out of ten Hondurans knew that Zika can be transmitted by the bite of a mosquito; however, only 2 and 0.1 percent, respectively, were aware that Zika can be spread by sexual intercourse and from a pregnant woman to her fetus. In total, four out of ten Hondurans knew that there is a causal relationship between Zika and microcephaly in newborns, and three out of ten knew that there is an association between Zika and Guillian-Barré syndrome. Overall, 50 percent of respondents said that they did not have enough information about the disease. Social implications: The findings of this study clearly identify information priority gaps that need to be urgently addressed by national stakeholders involved in public health activities to protect the most vulnerable population against Zika disease and its complications. Originality/value: This study is the first of its kind in Central America to inform any national risk communication strategy since the inception of the ZIKV response, particularly among at risk populations.